Diverse roles of UBE2S in cancer and therapy resistance: Biological functions and mechanisms - Mengjun Zhang; Jialin Wang; Zidi Zhang; Yan Guo; Xueling Lou; Lindong Zhang (Heliyon, 2024)
The Ubiquitin Conjugating Enzyme E2 S (UBE2S), was initially identified as a crucial member in controlling substrate ubiquitination during the late promotion of the complex's function. In recent years, UBE2S has emerged as a significant epigenetic modification in various diseases, including myocardial ischemia, viral hepatitis, and notably, cancer. Mounting evidence suggests that UBE2S plays a pivotal role in several human malignancies including breast cancer, lung cancer, hepatocellular carcinoma and etc. However, a comprehensive review of UBE2S in human tumor research remains absent. Therefore, this paper aims to fill this gap. This review provides a comprehensive analysis of the structural characteristics of UBE2S and its potential utility as a biomarker in diverse cancer types. Additionally, the role of UBE2S in conferring resistance to tumor treatment is examined. The findings suggest that UBE2S holds promise as a diagnostic and therapeutic target in multiple malignancies, thereby offering novel avenues for cancer therapy.